Push [videorecording (DVD)] - Davidge, Neil (Summit Entertainment, 2009)
Nick is a 'mover' - someone who can move things with his mind. He meets up with Cassie who is a 'watcher' - someone who can predict the future. She is trying to rescue her mother from the government. As they try to piece things together, Kira enters their lives. Kira is a 'pusher' - someone who can influence the thoughts of others. She has had a relationship with Nick and is the only person to survive a powerful 'enhancement' drug that was administered to her by the sinister Company. Now, the Company is after her, and Nick and Cassie will need to help her if they want to survive.